Encounters with Hellenism : studies on the First letter of Clement - Breytenbach, Cilliers, 1954-; Welborn, L. L., 1953- (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2004)
This volume deals with the encounter of Early Christianity with Hellenistic culture, particularly with the question of ancient rhetorical influence on the First Letter of Clement. It contains reprints of two classical studies by A. von Harnack and W. Jaeger, which were seminal for the understanding the letter against a Hellenistic background, furthermore it makes an important essay of the Dutch scholar W.C. van Unnik on the literary and rhetorical genre of First Clement ( genos symbouleutikon ) for the first time available in English. The editors also present two new studies: Breytenbach describes the Hellenistic background of Clement's use of metaphorical language and Welborn questions the traditional dating of First Clement on the basis of an analysis of the rhetorical situation.